Laser Induced Fluorescence Spectroscopy of Atoms in a Hollow Cathode Discharge Lamp - Agung Bambang Setio Utomo; Hans Helmut Telle (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
It has been demonstrated in this work that commercial hollow cathode discharge lamps can be used for LaserInduced Fluorescence technique by sending the laser beam into the cathode discharge lamp. Experiments havebeen performed using a single mode diode laser to investigate selected lines of argon ( 772 nm). After resonantlaser excitation on a certain transition, most of the other lines in the spectrum change their intensities in the LIFexperiment. The highest intensity increment is observed for the wavelengths which originate from the sameexcited level (2p7) as the one accessed by the pumping radiation. Further very strong intensity changes areobserved for transitions from the excited levels nearest to the pumping level, obviously due to collisional transferprocesses.